(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
The problems of development of innovative activity of Republic of Kazakhstan are analysed in this article. Innovative activity is one of reasons of economic development. In our country basic direction of development of innovation is integration of sciences and productions, introduction of scientific achievements in business environment. It is necessary to develop institutes that provide development and placing new to technology, also are basis of forming and realization of innovative politics of the state.